Pemanfaatan Gemini AI sebagai Sarana Pemberi Informasi di Bidang Pendidikan - Prakoso, Ario Adi; Nugroho, Febrian Radya (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2025)
The advanced development of Artificial Intelligence has created many platforms. One of the mostpopular Artificial Intelligence platforms in Indonesia is Gemini. However, the appearance of Gemini is notalways accepted in society. Some countries in the world take steps to block or restrict Gemini. This is becauseGemini can create plagiarism, and make people unable to think critically. This research aims to identifyGemini's ability as a means of providing information in the field of education. This research uses QualitativeMethod with Case Study approach. The result of the research is that the information generated by Gemini isnot always accurate. but based on testing Gemini by comparing information on the Alodokter website, Geminican provide accurate information even though the opportunity for misinformation can still occur. Therefore,it can be concluded that the use of Gemini as a means of providing information in the field of education thatdiscusses health can be applied, but only as additional information that does not yet have truth value beforecomparing it with trusted sources.Keywords: gemini, information, health, education